Angiopoietin‐2 in acute myocardial infarction complicated by cardiogenic shock—a biomarker substudy of the IABP‐SHOCK II‐Trial. (3rd September 2015) - Pöss, Janine; Fuernau, Georg; Denks, Daniel; Desch, Steffen; Eitel, Ingo; de Waha, Suzanne; Link, Andreas; Schuler, Gerhard; Adams, Volker; Böhm, Michael; Thiele, Holger
Abstract : Aims: Angiopoietin‐2 (Ang‐2) is a mediator of capillary leakage, and increased Ang‐2 levels were associated with poor in‐hospital outcome in a pilot study in cardiogenic shock (CS). In this larger study, we followed this hypothesis and aimed at assessing the predictive role of Ang‐2 on short‐ and long‐term mortality, investigating the effect of intra‐aortic balloon pump (IABP) treatment on Ang‐2 levels, and identifying clinical and procedural predictors of increased Ang‐2. Methods and results: In the IABP‐SHOCK II‐trial, 600 patients with CS complicating acute myocardial infarction were assigned to therapy with or without IABP. This substudy included 189 randomized patients with serial blood sampling performed at days 1, 2, and 3. No significant differences in Ang‐2 levels were found between patients with or without IABP. The Ang‐2 levels above the median at day 1 were associated with 30‐day [hazard ratio (HR) 1.98, 95% confidence interval (CI) 1.26–3.10, P = 0.002) and 1‐year mortality (HR 2.21, 95% CI 1.49–3.27, P < 0.001). Stratification of patients according to Ang‐2 levels at day 3 increased these associations (30 days HR 5.15, 95% CI 2.80–9.45, P < 0.001; 1 year HR 5.24, 95% CI 3.19–8.58, P < 0.001). The Ang‐2 concentrations were independent predictors for mortality in multivariate analysis (30 days HR 4.82, 95% CI 1.52–15.23, P = 0.007; 1 year HR 2.01, 95%CI 1.24–3.24, P = 0.005). Predictors of increased Ang‐2 levels at day 3 were baseline Ang‐2, development of acute kidney injury, bleeding events or transfusion, and impaired reperfusion. Conclusion: In CS, high levels of Ang‐2 are independently associated with poor short‐ and long‐term outcome and associated with the reperfusion success as well as complications. Clinical Trial Registration: URL:www.clinicaltrials.gov ; unique identifier: NCT00491036